THE FUNCTIONAL ANALYSIS OF MAIZE PRODUCTION AND THE EFFECT OF LANDCONSOLIDATION ON THE PRODUCTIVITY IN RWANDA - Fidele Hakorimana; Handan Akcaoz (Journal of Animal and Plant Sciences, 2018)
The main objective of this research was to evaluate the impact of land consolidation on the productivity of smallholder maize farmers in Rwanda. The research was conducted in Musanze District with a sample size of 67 farmers known to be adopting Land Consolidation in two sectors namely Cyuve and Nyange whereby the maize crop was grown due to favorable climate. The Cobb-Douglass production function model was used to estimate the productivity in maize production. The results showed that the land under maize cultivation, fertilizers and labor have a significant and positive influence on maize farm productivity; maize seed was not significant but has a partial positive influence on maize yield. On the productivity model, the results showed that age, years of schooling, extension access, and cooperative farming have a significant impact on the productivity but farmer’s experience was not significant and positively affected the productivity of maize farmers. The most constraints observed were the lack of adequate market, low price given to maize farmers compared to the cost of production, and price unpredictability of agricultural products. This study proposes strategies such as farmer training programs, raising the educational level of farmers, and providing farmers with greater access to credit, adoption contracting farming where farmers could produce on contractual basis with the known potential buyers and encourage cooperative farming which could increase the bargaining power to afford better prices in order to increase the productivityof fragmented maize farms in the region.
Keywords: Land consolidation; Cobb-Douglass; Maize Production; Smallholder farmers